Is There a Role for Second Line Therapy in Advanced Pancreatic Cancer? - Choi, Minsig; Saif, Muhammad Wasif; Kim, Richard (JOP. Journal of the Pancreas, 2014)
FOLFIRINOX (5-FU, oxaliplatin and irinotecan) and gemcitabine based regimens are widely used for the first-line treatment for patients with advanced pancreatic adenocarcinoma. Nab-paclitaxel and gemcitabine has replaced the use of many single agent gemcitabine in these patients population. In patients who progress on the first line therapy use of either 5-FU, leucovorin and oxaliplatin (FOLFOX) or gemcitabine and nab-paclitaxel combination has become a de facto standard depending on the chemotherapy they received in first line. Progress made in first line chemotherapy has lead to more interest in refractory pancreatic cancer. This article examines the 2014 American Society of Clinical Oncology (ASCO) Gastrointestinal Cancers Symposium regarding recent developments in the treatment of refractory pancreatic cancer, as these were presented in Abstracts #296, #297, #337, #344, and #381 of the meeting. Image: Chemotherapy regimens tested in refractory pancreatic cancer at 2014 ASCO GI Symposium